Asset-based Approach Community Service for Developing Digital Textbook in Secondary Language (L2) Teacher Education - Madjid, Hilda Izzati; Safriani, Afida; Rakhmawati, Rakhmawati (Department of English Language Education, UIN Sunan Ampel Surabaya, 2023)
ABSTRACT Service learning embedded in the course plays a vital role in transforming theoretical knowledge into practical one. It provides students with the concept and brings them in contextualizing their concept that they have already learned in the classroom. This study explores the process of enacting service learning using asset-based approach to university-community engagement. This study employed multiple data sets from observation, semi-structured interviews with teachers and principles, focused group discussion with students, and students’ products of digital textbooks. The findings revealed that service learning using the asset-based approach empowered all the stakeholders and contributed to emergence of the equitable partnership between university and community. The students’ product of a digital textbook represents collaboration between English teachers, the teacher educator, and the university students who successfully designed learning resources that meet the academic level and interests of students of the school partners. Keywords: Asset-Based Community Development (ABCD), Service Learning, Digital learning resources, Digital literacy